COURT PRACTICE OF APPLICATION OF CRIMINAL LEGAL MEASURES FOR IMMEDIATE COMMITMENT OF A CRIMINAL OFFENSE - Omelchuk, Oleg; Zakharchuk, Viktor (Socio-economic relations in the digital society, 2023)
The article analyses the judicial practice of applying criminal-legal measures for the indirect execution of a criminal offense. It has been established that the courts take into account the fact of indirect execution of a criminal offense when characterizing the person of the culprit and determining his social danger, namely, appoint a more severe punishment from the list of alternatives or appoint a punishment above the lower limit. At the same time, the courts quite often exempt such persons from serving a probationary sentence. At the same time, general types of exemption from criminal liability are practically not applied. This is due to the fact that, in the vast majority, intentional acts are committed in this way - minor crimes, while the condition for applying many types of exemption from criminal liability is the commission of a careless minor criminal offense. Most often, the courts classify cases of the commission of a criminal offense by means of indirect execution using a minor under the relevant article of the Special Part of the Criminal Code of Ukraine and under Art. 304 of the Criminal Code of Ukraine as the involvement of minors in criminal and illegal activities. However, quite often it is also taken into account as a circumstance that aggravates the punishment, which is very controversial. In some cases, in the case of indirect execution of a criminal offense using a minor, the courts may consider this only as a circumstance that aggravates the punishment. In cases where a minor who is involved by a criminal in the performance of the objective side of the act understands the real nature of his actions, certain coercive measures of an educational nature can be applied to such a person.  Such measures of a criminal legal nature, such as coercive measures of a medical nature, coercive treatment, or coercive measures of an educational nature in the case of indirect execution of a criminal offense do not have any differences from the general procedure for applying these measures to the guilty person.
Keywords: indirect execution of a criminal offense; measures of a criminal-legal nature; punishment